Combined nerve/muscle/skin biopsy could increase diagnostic sensitivity for vasculitic neuropathy. Issue 3 (24th April 2015) - Masuda, Hiroki; Misawa, Sonoko; Arai, Kimihito; Oide, Takashi; Shibuya, Kazumoto; Isose, Sagiri; Sekiguchi, Yukari; Nasu, Saiko; Mitsuma, Satsuki; Kuwabara, Satoshi
Abstract Objective Combined nerve/muscle biopsy is widely carried out to improve the diagnostic sensitivity for vasculitic neuropathy. However, an additional yield of muscle biopsy is modest. Therefore, we investigated whether skin biopsy in combination with nerve/muscle biopsy increases the detection rate of vasculitis. Methods A total of 25 combined nerve/muscle/skin biopsy samples from patients with biopsy‐proven necrotizing vasculitis (n = 16) or clinically probable vasculitic neuropathy (n = 9) were reviewed. Specimens from the sural nerve, peroneus brevis muscle and skin were obtained simultaneously by a single incision. Results Skin biopsy substantially contributed to diagnosis of vasculitic neuropathy. Additional skin biopsy enhanced diagnostic sensitivity from 88% to 100% in patients with pathologically confirmed vasculitis (n = 16). Vasculitis was detected only in skin specimens from two of the entire cohort (n = 25). There were no complications related to skin collection, such as anastomotic leakage or wound infection. Conclusion Combined nerve/muscle/skin biopsy could be a less invasive option to improve the diagnostic sensitivity for vasculitis.